Type 2 Diabetes, Antidiabetic Medications, and Colorectal Cancer Risk: Two Case–Control Studies from Italy and Spain - Rosato, Valentina; Tavani, Alessandra; Gracia-Lavedan, Esther; Guinó, Elisabet; Castaño-Vinyals, Gemma; Villanueva, Cristina M.; Kogevinas, Manolis; Polesel, Jerry; Serraino, Diego; Pisa, Federica E.; Barbone, Fabio; Moreno, Victor; et al. (Frontiers in Oncology, 2016)
Background: Type 2 diabetes mellitus has been associated with an excess risk of colorectal cancer, although the time-risk relationship is unclear and there is limited information on the role of antidiabetic medications. Aim: We examined the association between type 2 diabetes, antidiabetic medications, and the risk of colorectal cancer, considering also duration of exposures. Methods: Data derived from two companion case-control studies conducted in Italy and Spain between 2007 and 2013 on 1,147 histologically confirmed colorectal cancer cases and 1,594 corresponding controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated by unconditional multiple logistic regression models, adjusted for socioeconomic factors and major potential confounding factors. Results: Overall, 14% of cases and 12% of controls reported a diagnosis of diabetes, corresponding to an OR of colorectal cancer of 1.21 (95% CI 0.95-1.55). The OR was 1.49 (95% CI 0.97-2.29) for a duration of diabetes of at least 15 years. The OR was 1.53 (95% CI 1.06-2.19) for proximal colon cancer, 0.94 (95% CI 0.66-1.36) for distal colon cancer, and 1.32 (95% CI 0.94-1.87) for rectal cancer. In comparison with no use, metformin use was associated with a decreased colorectal cancer risk (OR 0.47, 95% CI 0.24-0.92), while insulin use was associated with an increased risk (OR 2.20, 95% CI 1.12-4.33); these associations were stronger for longer use (OR 8.18 for ≥ 10 years of use). Conclusion: This study shows evidence of a positive association between diabetes and colorectal cancer, mainly proximal colon cancer. Moreover, it indicates a negative association between colorectal cancer and metformin use and a positive association for insulin use.